Pengaruh Lingkungan Bisnis, Kualitas Layanan, dan Inovasi Produk Terhadap Keberlanjutan Bisnis Digital Kedai Kopi di Kabupaten Tulungagung - Mokhamad Mirza Rizky Sahara; Hujjatullah Fazlurrahman; Ika Diyah Candra Arifah; Achmad Kautsar (Jurnal Ekonomika Dan Bisnis (JEBS), 2026)
This study aims to analyze the influence of the business environment, service quality, and product innovation on the digital business sustainability of coffee shops in Tulungagung Regency. The rapid growth of coffee shops, driven by the development of the digital economy, requires business owners to adapt to changes in technology, consumer behavior, and increasingly competitive market conditions. This study employs a quantitative approach using explanatory research methods. Data were collected by distributing questionnaires to 120 coffee shop owners or managers who maintain active digital channels. Data analysis was conducted using Structural Equation Modeling–Partial Least Squares (SEM-PLS). The results indicate that the business environment, service quality, and product innovation have a positive and significant impact on digital business sustainability. The business environment variable exerts the most dominant influence, with a coefficient of 0.499, followed by service quality (0.446) and product innovation (0.423). An R-Square value of 0.708 indicates that the three independent variables explain 70.8% of the variation in digital business sustainability. These findings demonstrate that the ability to adapt to changes in the business environment, along with improvements in service quality and continuous product innovation, are crucial factors in maintaining the sustainability of digital-based coffee shop businesses in Tulungagung Regency.